Parenting Style, Effect, Identity in Career Choice-Collectivisme Theory - Fika Dwi Mulia; Afdal Afdal; Rezki Hariko; Finda Yolanda (Universitas PGRI SUMATERA BARAT, 2025)
It’s influence on adolescent career development in a collectivist context, but only a few studies have succeeded in integrating these variables, namely parenting style, influence, identity. This article aims to analyze relevant research to determine parenting style, influence, identity in career choice-collectivism theory. This research is descriptive research with a systematic literature review (SLR) method. Literature data was obtained from several pages such as Google Scholar, Sinta Ristekbrin, and Garuda Ristekbrin. To review the data literature, the main keywords used are